Preparation method of self-cleaning ceramic membrane based on aluminum-containing sludge

The metal components in the sludge can be transformed by heat transformation through high -temperature burning technology, forming a ceramic film with a catalytic effect, solving the problem of waste of resources such as Si and Al in sludge, and realizing the self -cleaning and anti -pollution capacity of ceramic film. , Promote the sustainable development of sludge resource utilization and drinking water treatment technology.

CN119345909APending Publication Date: 2025-01-24CHANGZHOU UNIV

Patent Information

Application Number
CN202411458234.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, when using sludge to prepare ceramic membranes, it is difficult to effectively utilize effective ingredients such as Si and Al in the sludge, resulting in waste of resources and environmental pollution.

Method used

Through high -temperature burn technology, the metal components in the sludge have heat conversion under high temperature conditions, forming a ceramic film with a catalytic effect, so as to have a self -cleaning function.

Benefits of technology

The efficient utilization of metal composition in sludge has been realized. The ceramic film has the ability to clean and anti -pollution, which improves the utilization rate of sludge resourceization and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a self-cleaning ceramic membrane based on aluminum-containing sludge. The preparation method comprises the following steps: mixing and ball-milling the aluminum-containing sludge and a pore-forming agent, and pressing to obtain a ceramic membrane blank; and sintering the ceramic membrane blank at a high temperature of 1050-1100 DEG C by using a tubular furnace at a heating rate of 5 DEG C per minute, and after sintering, naturally cooling the membrane to room temperature to obtain the aluminum-containing sludge-based self-cleaning ceramic membrane. According to the method, metal substances contained in the sludge are reasonably utilized, the catalytic function of the metal substances is fully played, organic matters can be efficiently degraded in the membrane filtration process, heavy metals in the sludge can be immobilized, and the purposes of waste reduction, harmlessness and recycling are achieved. The prepared sludge-based ceramic membrane has a self-cleaning function and a better removal effect on membrane pollution, and the membrane cleaning efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic membrane preparation, and in particular relates to a method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge. Background Art

[0002] With the continuous development of urbanization, the water quality safety and water demand of drinking water are also increasing. The coagulation process is widely used worldwide as a conventional treatment unit for drinking water sources. However, the addition of aluminum salt coagulants will cause a large amount of aluminum-containing sludge to be produced in the process, which is usually landfilled after concentration and centrifugal dehydration. However, this solution faces a series of problems such as insufficient landfill space, increased costs, and high environmental risks, which are all key technical difficulties faced in the treatment of drinking water sources. In particular, the aluminum ions contained in the sludge after dehydration can be as high as about 10%~20%, and landfilling leads to a large amount of aluminum resources waste.

[0003] Among the many water plant sludge resource utilization schemes, preparing sludge into inorganic ceramic membranes is an effective way, which can not only achieve 100% recovery of aluminum resources, but also decompose and oxidize the organic matter and volatile substances in the sludge during the firing process to form a stable porous membrane structure. However, the existing technical solutions for preparing ceramics from sludge mostly focus on improving its porosity, filtration flux, mechanical strength and other properties, and the resource utilization rate of effective components such as Si and Al in the sludge needs to be improved.

[0004] The present invention targets the effective ingredients in sludge and explores the sintering temperature, firing environment and optimization scheme in the firing process of ceramic membranes, aiming to obtain a method for preparing self-cleaning ceramic membranes using sludge, so as to realize the resource utilization of sludge, solve the problem of sludge landfill, and provide a solution strategy for promoting the sustainable development of drinking water treatment technology. Summary of the invention

[0005] To solve the above problems, the purpose of the present invention is to provide a method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge. Specifically, it is a method of calcining at high temperature to thermally transform the metal components in the sludge under high temperature conditions, thereby having a catalytic effect and making the ceramic membrane have a self-cleaning function.

[0006] Due to the presence of various metals in sludge, such as transition metal elements such as iron (Fe) and magnesium (Mg), strong catalytic active sites with regular shapes will be formed during the preparation of ceramic membranes, so that the contaminated ceramic membranes can be activated to produce free radicals during the cleaning process using oxidants, thereby showing a more efficient pollutant removal effect, namely the self-cleaning effect.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows: A method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge comprises the following steps: (1) The dehydrated aluminum-containing sludge is crushed with a pulverizer until there are no obvious particles in the aluminum-containing sludge and it feels like flour when touched by hand; the aluminum-containing sludge is mixed with a pore-forming agent and put into a ball mill to fully grind to obtain a mixed powder; the particle size range of the ground mixed powder is 0.01 mm~0.1 mm.

[0008] (2) Pressing the mixed powder to obtain a ceramic membrane body; (3) The ceramic membrane blank is sintered at a temperature of 1050-1100°C in a tube furnace. The heating rate during sintering is 5°C per minute. Too slow a heating rate will make it unable to form sufficient density and reduce the porosity, while too fast a heating rate will produce uneven thermal gradients inside the material, resulting in high and low adhesion in local areas, affecting the quality of the sintered product. After sintering, the membrane is naturally cooled to room temperature to obtain an aluminum-containing sludge-based self-cleaning ceramic membrane.

[0009] Furthermore, the pore-forming agent in step (1) accounts for 30-40% of the total mass of the aluminum-containing sludge and the pore-forming agent.

[0010] Furthermore, the pore-forming agent in step (1) includes but is not limited to corn starch, sawdust, coal powder, polystyrene, etc.; preferably corn starch.

[0011] Furthermore, the aluminum-containing sludge in step (1) has an Al content of 10%-35% and a Si content of 5%-25%.

[0012] Furthermore, the specific steps of step (2) are: using a mold with a diameter of 30 mm and a hydraulic press to press the mixture at a pressure of 100 to 400 kPa for 3 to 7 minutes to obtain a dry blank of the ceramic membrane, the thickness of which ranges from 2 to 4 mm.

[0013] Furthermore, the sintering temperature in step (3) is 1050° C. and the holding time is 2 h.

[0014] The self-cleaning ceramic membrane prepared by the above method was tested by a cross-flow membrane filtration device to compare the water permeability of the prepared ceramic membrane. The catalytic and self-cleaning efficiency was verified by monitoring the change of transmembrane pressure (TMP) through a methylene blue degradation filtration experiment. The results showed that the aluminum-containing sludge-based ceramic membrane prepared by the method of the present invention has self-cleaning and anti-pollution capabilities, as well as high water permeability performance.

[0015] The present invention has the following beneficial effects: (1) The sludge used in the present invention comes from the solid waste of the tap water treatment plant. The sludge-based ceramic membrane prepared in the present invention can reasonably utilize the metal substances contained in the sludge and give full play to its catalytic function. It can efficiently degrade organic matter during the membrane filtration process and fix the heavy metals in the sludge, thereby achieving the goals of waste reduction, harmlessness and resource utilization.

[0016] (2) Due to the self-cleaning function of the sludge-based ceramic membrane prepared by the present invention, the ceramic membrane can be activated to generate free radicals during the cleaning process using an oxidant, thereby showing a better removal effect on membrane contamination and improving the membrane cleaning efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart for preparing a self-cleaning ceramic membrane; Figure 2 This is a schematic diagram of the self-cleaning ceramic membrane filtration experimental device; Figure 3 XRD pattern of the self-cleaning ceramic membrane (a) and the main components of the self-cleaning ceramic membrane (b). DETAILED DESCRIPTION

[0018] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention are further described in detail below with reference to the accompanying drawings.

[0019] The aluminum-containing sludge was dried in a fluidized bed dryer at 120°C for 8 hours, fully dehydrated, and crushed into powder using a pulverizer. After crushing, the aluminum-containing sludge had no obvious particles and felt like flour when touched by hand. The chemical composition of the sludge was analyzed by XRF as shown in Table 1.

[0020] Table 1 Content of each element in sludge

[0021] The corn starch used in the following examples of the present invention is sourced from Wuxi Yatai United Chemical Co., Ltd.

[0022] The raw materials or reagents not otherwise specified in the present invention are all commercially available products. Embodiment 1

[0023] 1.4g of aluminum-containing sludge powder was mixed with 0.6g of corn starch (pore-forming agent), and the mixture was fully ground in a ball mill to reduce the particle size. The particle size of the ground particles was 50-80μm. The mixture was pressed at a pressure of 200 kPa using a circular mold with a diameter of 30mm and maintained for 5 minutes. The obtained ceramic membrane blank was 30mm in diameter and 2mm in thickness. The ceramic membrane blank was placed in a tubular furnace and heated to 1050°C at a heating rate of 5°C / min, and kept warm for 2 hours. After naturally cooling to room temperature, a sludge-based self-cleaning ceramic membrane was obtained. Embodiment 2

[0024] The difference between this embodiment and the first embodiment is that 1.6 g of aluminum-containing sludge powder is mixed with 0.4 g of corn starch, and the other operations are the same as those in the first embodiment. Embodiment 3

[0025] The difference between this embodiment and the first embodiment is that 1.2 g of aluminum-containing sludge powder is mixed with 0.8 g of corn starch, and the other operations are the same as those in the first embodiment. Embodiment 4

[0026] When the film forming conditions are the same as those in Example 1, the sintering temperature is changed to 1100° C. and the rest of the temperature control procedures are the same as those in Example 1. Comparative Example 1

[0027] When the film forming conditions are the same as those in Example 1, the sintering temperature is changed to 900° C. and the rest of the temperature control procedures are the same as those in Example 1. Comparative Example 2

[0028] When the film forming conditions are the same as those in Example 1, the sintering temperature is changed to 1000° C. and the rest of the temperature control procedures are the same as those in Example 1. Comparative Example 3

[0029] When the film forming conditions are the same as those in Example 1, the sintering temperature is changed to 1200° C. and the rest of the temperature control procedures are the same as those in Example 1. Comparative Example 4

[0030] When the film forming conditions were the same as those in Example 1, the heating rate of sintering was adjusted to 3°C / min, the temperature was raised to 1050°C, and kept at this temperature for 2 hours. Comparative Example 5

[0031] When the film forming conditions were the same as those in Example 1, the sintering heating rate was adjusted to 10°C / min, the temperature was raised to 1050°C, and kept at this temperature for 2 hours.

[0032] Water permeability is one of the basic properties of ceramic membranes. Highly permeable ceramic membranes can reduce the operating pressure during actual use and save the operating cost of ceramic membranes. Figure 2 ) for filtration, and the membrane flux was set to 8.64×10 -4 m / s, monitor the transmembrane pressure difference TMP of the ceramic membranes prepared in the above embodiments and comparative examples, and further calculate their water permeability in the deionized water filtration process.

[0033] The specific results of the water permeability test are shown in the following table. The difference between Examples 1, 2, and 3 is the ratio of sludge to pore-forming agent added. In Example 2, due to the low content of pore-forming agent, the prepared ceramic membrane cannot form enough membrane pores, resulting in its water permeability being discounted compared to Examples 1 and 3. The water permeability of Example 1 and Example 3 did not change much, but Example 1 is more economical. The water permeability of Comparative Examples 1 and 2 is lower than that of Example 1. Although Comparative Example 3 has a higher water permeability, its deformation during the calcination process is too large, resulting in a lower strength of the ceramic membrane, which is not suitable for promotion and application. Comparative Example 4 has a too slow heating rate, resulting in insufficient pores during the membrane firing process, and the water permeability is much lower than that of Example 1. Comparative Example 5 has a too fast heating rate, making it difficult to form a complete membrane during the membrane making process, and its membrane yield is only 12%. Therefore, the self-cleaning ceramic membrane fired at 1050°C described in Example 1 is the best choice.

[0034] Table 2 Water permeability of self-cleaning ceramic membranes prepared at different temperatures

[0035] The self-cleaning performance of the ceramic membrane prepared in Example 1 was tested to investigate the degradation and removal of organic matter in the presence of hydrogen peroxide. A 10 mg / L methylene blue aqueous solution was used as the influent and the filtration flux was set to 8.64×10 -4 m / s, hydrogen peroxide concentration ≤7.5%±0.3%, the test shows that the effluent concentration of methylene blue is about 0.1 mg / L, and the removal rate can reach more than 99%, indicating that the membrane has catalytic cleaning function (residence time in the membrane is less than 10s). During this process, the transmembrane pressure difference TMP did not increase significantly, showing excellent anti-pollution ability.

[0036] Table 3 Self-cleaning efficiency of self-cleaning ceramic membranes at different sludge pore-forming agent contents and temperatures

[0037] According to the above test process, Example 3 and Example 4 were tested. In Example 3, due to the reduction in the amount of sludge, the amount of SiO2 generated during the membrane firing process was insufficient, resulting in a decrease in the removal rate, and the self-cleaning performance was inferior to that of Example 1. In Example 4, the sludge content was the same as that of Example 1, and its sintering temperature was 1100°C. The removal rate of its methylene blue aqueous solution was measured to be 80%, which was lower than that of Example 1. In summary, it can be found that the sintering temperature has a certain influence on the self-cleaning performance of the self-cleaning ceramic membrane.

[0038] Figure 3 (a) is the XRD pattern of the self-cleaning ceramic membrane. It can be seen from the figure that the diffraction peaks at 42.3° and 43.7° are aligned with the (210) and (220) planes of graphite carbon (ICSD No.97-002-7422), while the diffraction peaks at 20.8°, 26.6° and 50.1° correspond to the (100), (011) and (112) planes of SiO2 (ICSD No.97-018-2994), which indicates that SiO2 and crystalline carbon exist in the prepared membrane, which is beneficial to catalytic self-cleaning.

[0039] Figure 3 (b) is the main component of the self-cleaning ceramic membrane. It can be seen from the figure that under the sintering condition of 1050℃, its main components are C, SiO2 and Al2(SO4)O.

[0040] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge, characterized in that: The specific steps include: (1) Grinding the dehydrated aluminum-containing sludge; mixing the aluminum-containing sludge with a pore-forming agent, and grinding them in a ball mill to obtain a mixed powder; the particle size of the ground mixed powder ranges from 0.01 mm to 0.1 mm; (2) Pressing the mixed powder to obtain a ceramic membrane body; (3) The ceramic membrane blank is sintered at a temperature of 1050-1100°C in a tubular furnace at a heating rate of 5°C per minute. After sintering, it is naturally cooled to room temperature to obtain an aluminum-containing sludge-based self-cleaning ceramic membrane.

2. The method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge according to claim 1, characterized in that: The pore-forming agent in step (1) accounts for 30-40% of the total mass of the aluminum-containing sludge and the pore-forming agent.

3. The method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge according to claim 1, characterized in that: The pore-forming agent in step (1) is selected from one or more of corn starch, sawdust, coal powder, and polystyrene.

4. The method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge according to claim 1, characterized in that: The aluminum-containing sludge in step (1) has an Al content of 10%-35% and a Si content of 5%-25%.

5. The method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge according to claim 1, characterized in that: The specific steps of step (2) are: using a mold with a diameter of 30 mm and a hydraulic press to press the mixture at a pressure of 100 to 400 kPa for 3 to 7 minutes to obtain a dry blank of the ceramic membrane, the thickness of which ranges from 2 to 4 mm.

6. The method for preparing a self-cleaning ceramic membrane based on aluminum-containing sludge according to claim 1, characterized in that: The sintering temperature in step (3) is 1050°C and the holding time is 2h.

7. Aluminum-containing sludge-based self-cleaning ceramic membrane prepared by the method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for sintering porous ceramic material by city sludge

    CN104355674A

  • Method for preparing foamed ceramics by utilizing sludge pyrolytic residues and equipment by utilizing method

    CN107434429A

  • Ceramic membrane and production method thereof

    CN108479419A

  • Micro-filtration ceramic membrane using waste materials as raw materials and preparation method thereof

    CN108546149A

  • Double-layer ceramic membrane and preparation method thereof

    CN110577405A

Cited By

  • Preparation method of ceramic membrane based on algae-containing sludge endogenous pore forming and catalysis

    CN120115016A

  • A preparation method of a ceramic membrane based on endogenous pore forming and catalysis of algal-containing sludge

    CN120115016B